Multilevel voltage source conversion approach: multiplexed choppers. Issue 12 (1st October 2016) - Burguete, Eduardo; Lopez, Jesus; Zubimendi, Ignacio; Larrazabal, Igor; Meynard, Thierry; Gateau, Guillaume
Abstract : In the past two decades, many different multilevel converters have been presented. Usually, these comprise a large number of semiconductors. Some converters try to reduce the amount of semiconductors by using some of them for the three phases. This study presents a different approach: a converter where all the switching semiconductors are common for the three phases. This approach reduces the amount of high‐frequency switching semiconductors and can use cheaper semiconductors for low‐frequency switching ones, which may lead to a reduction of the total cost of the converter. Different options are described throughout this study and the advantages and disadvantages of each one of them are discussed. Finally, some simulation results illustrate the correct operation of the proposed new topology.